2013
DOI: 10.1080/01635581.2013.741755
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Nutritional Status and the Glasgow Prognostic Score in Patients with Cancer of the Esophagus and Stomach

Abstract: A relationship between weight loss and inflammation has been described in patients with cancer. In the present study, the relationship between subjective global assessment (SGA) and the severity of inflammation, as defined by Glasgow prognostic score (GPS), as well as the relationship of both of these measures with the presence of complications and survival time, was assessed. In addition, we compared the diagnosis given by SGA with parameters of nutritional assessment, such as body mass index, triceps skinfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 18 publications
1
27
1
3
Order By: Relevance
“…Paceli et al 28 found a preoperative weight loss greater than 10% in 42% of gastric cancer patients, similar to those of other Asian studies, of 13% and 31% 6,7 , respectively. However, this incidence may increase to 81% in the postoperative period, which confirms that gastrectomy significantly affects nutrition 20,29 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Paceli et al 28 found a preoperative weight loss greater than 10% in 42% of gastric cancer patients, similar to those of other Asian studies, of 13% and 31% 6,7 , respectively. However, this incidence may increase to 81% in the postoperative period, which confirms that gastrectomy significantly affects nutrition 20,29 .…”
Section: Discussionmentioning
confidence: 86%
“…A Brazilian group found a relationship between PGSGA and GPS, and both measures were associated with postoperative complications and survival in patients with esophageal and stomach cancer 29 . An ongoing study in our research group is evaluating the role of GPS as a short-term predictor of worsening nutritional status and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Subjective Global Assessment (SGA), a questionnaire based on four parameters of patient's history (percentage of weight loss, changes in habitual diet, presence of significant gastrointestinal symptoms, and changes in patient's functional capacity) and three elements of their physical examination (loss of subcutaneous fat, muscle wasting, and presence of edema or ascites) is one the most commonly used tool for nutritional screening in malnourished hospital patients with cancer. SGA is strongly correlated with performance status in esophageal cancer patients [16] as well as with The Glasgow prognostic score and with complications during cancer treatment [23]. Other tools that have been studied in cancer patients is the Prognostic Nutritional Index (PNI), the Nutritional Risk Screening 2002 (NRS 2002), the Controlling Nutritional Status (CONUT) and the Nutritional Risk Index (NRI).…”
Section: Methods Of Nutritional Assessment and Impact On Clinical Outmentioning
confidence: 99%
“…Tumors located in different portions of the gastrointestinal tract are among the most common in the world, and the associated risk factors are changes in the lifestyle of modern society, characterized by the interaction between alcoholism, smoking, obesity, physical inactivity, and poor diet, with high consumption of nitrates and low fiber intake 3 , 4 . Nutritional depletion is a common diagnosis, and it has been related to worse outcomes and cancer progression 5 . ‐ 7…”
Section: Introductionmentioning
confidence: 99%